2021
DOI: 10.3390/idr13010001
|View full text |Cite
|
Sign up to set email alerts
|

Acute Brucellosis with a Guillain-Barre Syndrome-Like Presentation: A Case Report and Literature Review

Abstract: Introduction: Brucellosis is a zoonotic disease that can affect the central and peripheral nervous system and it has variable neurological manifestation. However, brucellosis infection that presents with acute peripheral neuropathy mimicking Guillain-Barre syndrome (GBS) is rarely reported in the literature. Objective and method: We report a 56-year-old man who was initially diagnosed with GBS, and then he was confirmed to have acute Brucella infection. We also did a systematic literature review to study the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Brucellosis is a disease that can affect the central and peripheral nervous system, and it has variable neurological manifestations. However, brucellosis infection that presents with acute peripheral neuropathy mimicking GBS-like manifestations was reported among 19 cases according to Alanazi et al [ 15 ] Although our patient had confirmed signs of peripheral neuropathy, his presentation lacks any signs of meningitis, encephalitis, brain abscess, myelitis, or radiculitis, commonly seen in neurobrucellosis. It is recommended to investigate for Brucella among patients in endemic regions presenting with acute peripheral neuropathy [ 15 ].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Brucellosis is a disease that can affect the central and peripheral nervous system, and it has variable neurological manifestations. However, brucellosis infection that presents with acute peripheral neuropathy mimicking GBS-like manifestations was reported among 19 cases according to Alanazi et al [ 15 ] Although our patient had confirmed signs of peripheral neuropathy, his presentation lacks any signs of meningitis, encephalitis, brain abscess, myelitis, or radiculitis, commonly seen in neurobrucellosis. It is recommended to investigate for Brucella among patients in endemic regions presenting with acute peripheral neuropathy [ 15 ].…”
Section: Discussionmentioning
confidence: 59%
“…However, brucellosis infection that presents with acute peripheral neuropathy mimicking GBS-like manifestations was reported among 19 cases according to Alanazi et al [ 15 ] Although our patient had confirmed signs of peripheral neuropathy, his presentation lacks any signs of meningitis, encephalitis, brain abscess, myelitis, or radiculitis, commonly seen in neurobrucellosis. It is recommended to investigate for Brucella among patients in endemic regions presenting with acute peripheral neuropathy [ 15 ]. On the other hand, peripheral neuropathy is a frequent finding in AAV and may occur in up to 70% of patients with microscopic polyangiitis and 15% of patients with granulomatosis and polyangiitis [ 16 ].…”
Section: Discussionmentioning
confidence: 59%
“…Peripheral nervous system involvement occurs in 7% of neurobrucellosis cases 21 . Acute, subacute, or chronic polyradiculoneuropathies, some without sensory involvement or mimicking Guillain-Barré syndrome, have been described in case reports 21 , 22 .…”
Section: Neurological Manifestationsmentioning
confidence: 99%
“…One patient (5.3%) died, and 16 patients (84.2%) recovered their walking ability. Walking recovery time varied from two weeks to one year [ 12 ].…”
Section: Discussionmentioning
confidence: 99%